Hubungan Jenis Persalinan dan Prematuritas dengan Kejadian Asfiksia Neonatorum di RSUD Bangkinang - Nurzaihan, Nurzaihan; Harahap, Dewi Anggriani; Nislawaty, Nislawaty (Evidence Midwifery Journal, 2025)
Neonatorum neonatal asphyxia is the failure of the baby to perform regular and spontaneous breathing after birth. Factors causing neonatal neonatal asphyxia include antepartum, intrapartum, and fetal factors. The purpose of the study was to determine the relationship between the type of labor and prematurity with the incidence of neonatal asphyxia at RSUD Bangkinang. This type of research uses Observational Analytics  with Case Control research design. The study will be conducted on June 14-22, 2023. The study population of all newborn medical record data at Bangkinang Hospital in 2021-2022 was 858 babies. The sample used a ratio of 1: 1, namely 60 samples of infants experiencing asphyxia neonatorum and 60 samples of infants not experiencing asphyxia neonatorum. Case group retrieval and control techniques using Total Sampling and Systematic Random Sampling. Data collection tools using Checklist sheets. Data analysis used univariate and bivariate analysis using Chi Square test. The results of the study showed a relationship between the type of delivery  (ρ value = 0.001)  and prematurity (ρ value = 0.002)  with the incidence of neonatal asphyxia at Bangkinang Hospital in 2021-2022. It is expected that pregnant women routinely make Antenatal Care  visits so that the risk of causing neonatal asphyxia from maternal factors, namely the type of labor and fetal factors, namely premature gestational age, can be prevented and treated as early as possible.